Democratizing Electricity in Nepal: NACEUN is Lighting up one Community at a Time - Editor, The (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
No Abstract DOI: http://dx.doi.org/10.3126/hn.v10i0.7123 Hydro Nepal Vol.10 January 2012 88-89